Is space war imminent? Exploring the possibility. Issue 5 (20th October 2017) - Handberg, Roger
ABSTRACT: A resurgence is occurring regarding the possibility of armed conflict in outer space. At a certain level, these new assertions regarding the possibilities of space war mirror similar arguments at the dawn of the space age. That enthusiasm for arming the heavens dissipated under the reality of conducting such operations proving extraordinarily difficult and expensive. Instead, the concept of a space sanctuary through international treaty and calculations of national interest became the norm. Recent actions and words by powers new to military space operations are generating a counterresponse by the United States. This study pursues the policy ramifications of changes in the understandings that characterize the current international space legal regime. Essential to understanding the new space order is the reality that the military space community now contains more members than the original two, the U.S. and the Soviet Union. The situation becomes a multisided game with profound implications in terms of budget, military organization and strategy, and politics. All this occurs in a situation of increasing international participation in space operations nominally commercial in nature. Commercial space applications hold the promise of allowing states to "skip" the developmental process by providing shortcuts not available previously.